2015
DOI: 10.7567/jjap.54.04da04
|View full text |Cite
|
Sign up to set email alerts
|

Atomically flattening of Si surface of silicon on insulator and isolation-patterned wafers

Abstract: By introducing high-purity and low-temperature Ar annealing at 850 °C, atomically flat Si surfaces of silicon-on-insulator (SOI) and shallow-trench-isolation (STI)-patterned wafers were obtained. In the case of the STI-patterned wafer, this low-temperature annealing and subsequent radical oxidation to form a gate oxide film were introduced into the complementary metal oxide semiconductor (CMOS) process with 0.22 µm technology. As a result, a test array circuit for evaluating the electrical characteristics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…5(b) for the atomically flat device had no adverse impact on the charge to breakdown of MOS devices. The result is consistent with the results of improvement of E BD for the atomically flat device having STI edge previously reported (10), or the results of breakdown characteristics of the MOS capacitors having the field-oxide-etched isolation patterns (6,7), demonstrating that the …”
Section: Small Active Area and Its Edgesupporting
confidence: 92%
“…5(b) for the atomically flat device had no adverse impact on the charge to breakdown of MOS devices. The result is consistent with the results of improvement of E BD for the atomically flat device having STI edge previously reported (10), or the results of breakdown characteristics of the MOS capacitors having the field-oxide-etched isolation patterns (6,7), demonstrating that the …”
Section: Small Active Area and Its Edgesupporting
confidence: 92%
“…Other studies have reported that the Si surface morphology appears to change at annealing temperatures of around 900 °C. [23][24][25] A possible explanation is that the oxygen atoms in the oxide layer at the SiN/Si or SiN/poly-Si interface can start to move at around 900 °C, which allows the atomic bonding structure to drastically change according to the Si reconstruction process. 26 This may cause the dangling bond densities at the SiN/Si interface to increase and to be detected as Pb centers and/or the M signal exhibiting a local maximum peak at around 900 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The interface roughness degrades not only electron mobility [66][67][68][69][70][71] and gate dielectric reliability [72][73][74], but also noise generation [71,75,76]. An atomically flat interface [77][78][79][80][81][82][83][84] is effective for reducing low-frequency noise [79,[83][84][85][86][87].…”
Section: Mosfets With Atomically Flat Gate Insulator/si Interfacementioning
confidence: 99%